2015
DOI: 10.1071/fp14162
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric G-proteins involved in the MeJA regulated ion flux and stomatal closure in Arabidopsis thaliana

Abstract: Heterotrimeric G-proteins play an important role in plant signalling pathways. The plant hormone methyl jasmonate (MeJA) can induce stomatal closure in many plant species. The signal cascade in MeJA-induced stomatal closure has been studied previously. However, the function of G proteins in this process has not yet been evaluated. In this study, the stomatal movement induced by MeJA in the wild-type Arabidopsis thaliana (L. Heynh.) (WS), Gα subunit loss-of-function mutant gpa1–1 and gpa1–2 guard cells were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Net stomatal fluxes of Ca 2+ were measured with a non-invasive microsensing system (NMT100-SIM-XY/YG; Younger, USA) according to methods described by Sun et al (2009) and Yan et al (2015) with some modifications. Silanized glass micropipettes (4-5 mm aperture; XYPG120-2; Xuyue Science and Technology, Beijing, China) were first filled with a backfilling solution (100 mM CaCl 2 ), then the front of the micropipettes was filled with 40-50 mm of selective liquid ion exchanger to create the Ca 2+ -selective sensor.…”
Section: Measurement Of Net Fluxes Of Ca 2+ In Guard Cellsmentioning
confidence: 99%
“…Net stomatal fluxes of Ca 2+ were measured with a non-invasive microsensing system (NMT100-SIM-XY/YG; Younger, USA) according to methods described by Sun et al (2009) and Yan et al (2015) with some modifications. Silanized glass micropipettes (4-5 mm aperture; XYPG120-2; Xuyue Science and Technology, Beijing, China) were first filled with a backfilling solution (100 mM CaCl 2 ), then the front of the micropipettes was filled with 40-50 mm of selective liquid ion exchanger to create the Ca 2+ -selective sensor.…”
Section: Measurement Of Net Fluxes Of Ca 2+ In Guard Cellsmentioning
confidence: 99%
“…In turn, the accumulation of ROS activates the Ca 2+ channel and the resulting elevation of free cytoplasmic Ca 2+ triggers PM anion channels leading to cell depolarization (Pei et al ., ; Murata et al ., ). Our previous results on the relevant ion transporter genes also showed that MeJA upregulated the expression of the anion channel genes SLAC1 and SLAC3 (Yan et al ., ), which suggested that the anion channels were activated. The depolarization of the PM further promoted efflux of K + from the cell through the depolarization‐dependent outward K + channels (Schroeder et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Evans () indicated that exogenous MeJA treatment downregulated the inward K + channels but upregulated the outward K + channels. We observed the K + efflux triggered by MeJA in Col‐0 guard cells, combined with the upregulation of GORK , but downregulation of the inward K + channel gene KAT1 (Yan et al ., ), and this finally resulted in stomatal closure. However, when the PM H + ‐ATPase was inhibited or mutated, the K + efflux was attenuated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ion flux is calculated on the basis of Fick's law of diffusion, J 0 = ﹣ D ·( dc / dx ), where J 0 represents the ion flux (in units of pmol·cm −2 ·s −1 ), dc / dx is the ion concentration gradient, and D is the ion diffusion constant (in cm −2 ·sec −1 ) in a particular medium (Sun, Li, Yin, Shangguan, & Xu, ). Net K + , Na + , H + , and Ca 2+ fluxes during plant response to stresses were measured using an NMT system (NMT‐YG‐100; Younger USA LLC, Amherst, MA, USA; Sun, Chen, et al, ; Sun, Dai, et al, ; Yan, Luo, et al, ; Yan, McLamore, et al, ; Zhang et al, ). Prepulled silanized glass micropipettes (diameter = 4–5 μm, XY‐DJ‐01; Xuyue [Beijing] Science and Technology Co. Ltd., Beijing, China) were prepared and calibrated as described below.…”
Section: Methodsmentioning
confidence: 99%